1 | initial version |

Then let us solve with respect to x and z.

Essentially the same code gives the expected answer:

```
var( 'x, y, z, y0' )
eq1 = x^2 + y^2 == 4
eq2 = (y-y0)^2 + z^2 == 4
solutions = solve( [ eq1, eq2 ], [x, z] )
for solution in solutions:
print solution
```

And we get:

```
[x == -sqrt(-y^2 + 4), z == -sqrt(-y^2 + 2*y*y0 - y0^2 + 4)]
[x == sqrt(-y^2 + 4), z == -sqrt(-y^2 + 2*y*y0 - y0^2 + 4)]
[x == -sqrt(-y^2 + 4), z == sqrt(-y^2 + 2*y*y0 - y0^2 + 4)]
[x == sqrt(-y^2 + 4), z == sqrt(-y^2 + 2*y*y0 - y0^2 + 4)]
```

Copyright Sage, 2010. Some rights reserved under creative commons license. Content on this site is licensed under a Creative Commons Attribution Share Alike 3.0 license.